Characterisation of cv. Albarin Blanco (Vitis vinifera L.). Synonyms, homonyms and errors of identification associated with this cultivar - José-Luis Santiago; Susana Boso; Mar Vilanova; María del Carmen Martínez (OENO One, 2005)
Two grapevine types established in the collection of the Misión Biológica de Galicia (CSIC), both commonly called Albarín Blanco (type I and II), showed characteristics suggesting an error of homonymy. Varieties with similar characteristics to Albarín Blanco I, but with different names (Blanco País, Blanco Verdín, Blanco Legítimo, Raposo), were found in the Principality of Asturias (northern Spain) and Galicia (northwestern Spain). Ampelographic characterisation, agronomic and molecular analysis showed that Albarín Blanco I should be understood as the « true » Albarín Blanco, and that Blanco País, Blanco Verdín, Blanco Legítimo and Raposo are synonyms. Albarín Blanco II was found to be Savagnin Blanc, introduced into the area after the phylloxera epidemic in the 19th century.